Roma in the COVID-19 Crisis: Transformative Elements That Emerge from the Research - Diana Valero; Carmen Elboj; Lena De Botton (Social Sciences)
Research on the impact of the COVID-19 pandemic on the Roma community consistently demonstrates that it has exacerbated pre-existing social exclusion and marginalization. However, few studies have specifically addressed the transformative actions or strategies that helped to mitigate these adverse effects. This study aimed to identify and analyze transformative elements through a systematic review, following PRISMA guidelines. The search was conducted across Web of Science, SCOPUS, and Google Scholar, yielding 995 records, of which 46 were included in the final phase and 25 in our synthesis. Our analysis focused on community-led initiatives that addressed inequalities, particularly when Roma community members were involved in the design of solutions or took on mediation roles. The results underscore the critical importance of inclusive, community-driven actions in overcoming structural barriers and promoting long-term resilience within Roma communities during the pandemic.